150 years of Colonne Concerts - Douche, Sylvie (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
In the early decades of the 19th century, France created many Musical Societies with a dual objective: to offer (symphonic) music to the widest possible audience, and to perform a repertoire combining new works and masterpieces of the past. The Association artistique des Concerts Colonne is one such Society. Founded in 1873 by Édouard Colonne (1838–1910), the group took over from the short-lived Concert national invented by Georges Hartmann (1843-1900), while maintaining Sunday concerts in the Théâtre du Châtelet. Colonne quickly found itself in competition with the Concerts Lamoureux, making artistic choices that set it apart. Thanks to the posters and programs deposited in various repositories, we thought it would be interesting to take a sampling of these rich holdings to illustrate a history of the Ensemble that answers the following questions: what was its overall operation? How were programs and Hall Programs drawn up (e.g. by Charles Koechlin), and who were the musicians? In so doing, we will have sketched a (non-exhaustive) portrait of the Concerts Colonne, which will be blowing out its 150 candles in 2023. One of the longest-running concert series that brought together outstanding performers, composers, and a wide range of listeners was the Colonne Concerts series. Their leader, Édouard Colonne, has been organizing remarkable musical events that have opened up to the Parisian public both classical works by Beethoven, Mozart, Weber, and Schumann and works by contemporary composers, including Fauré, Debussy, d'Indy, Ravel, Charpentier, Widor, Chabrier, and Dukas.